Analysis of Social Skills on Elementary School Students in Rural and Urban Area - Moh Salimi; Ratna Hidayah; Muna Fauziah; Dewi Astuti; Anesa Surya; Nurham Hahsa (Jurnal Ilmiah Pendidikan Dasar, 2026)
Technological advancements have shifted students’ social interactions from in-person to virtual, challenging them to develop healthy social relationships and collaborative skills in line with the demands of 21st-century education. Therefore, this study aims to analyse the social skills of elementary school students in Kebumen and Purworejo Regencies, specifically in rural and urban areas. This study employs a mixed-methods design with an explanatory sequential approach. Samples were selected using cluster sampling for students and purposive sampling for teachers, resulting in 107 fifth-grade students and 4 homeroom teachers from five elementary schools representing both rural and urban areas. Data were collected through a social skills questionnaire containing 20 Likert-scale items and a semi-structured interview guide. Quantitative data were analysed using comparative descriptive statistics, while qualitative data were analysed thematically. The results indicated that the average total social skills scores of both groups were relatively comparable, yet they exhibited complementary profiles. Rural students excelled in cooperation (3.504) and self-control (3.451), rooted in a culture of mutual assistance and social harmony, while urban students significantly excelled in assertiveness (3.783), driven by a competitive learning environment and public speaking training programs. Responsibility indicators were relatively balanced in both regions, with more than 85% of students achieving the high category. These findings imply the need for context-specific educational strategies namely, strengthening self-reliance in rural areas without undermining the value of mutual cooperation, and fostering cooperation and empathy in urban areas through collaborative learning. Character education policies must be responsive to regional differences in order to comprehensively develop students’ social skills.